Levels of depression, anxiety and stress in undergraduate students practicing choir singing (Research, Society and Development, 2023)
Introduction: Undergraduate students face significant mental health issues during Higher Education, such as depression, anxiety and stress. In this sense, it is thought that sessions of choir singing can softy these issues. Methodology: This study analyzed the levels of depression, anxiety and stress in undergraduate students after four weekly choir singing sessions. Forty-five participants answered the questionnaire of sociodemographic conditions and the Depression, Anxiety and Stress Scale (DASS-21). The data obtained was statistical analyzed. Results: The analysis did not observe statistical significance (p